Successful autologous hematopoietic stem cell transplantation for a patient with rapidly progressive localized scleroderma. (March 2015) - Nair, Velu; Sharma, Ajay; Sharma, Sanjeevan; Das, Satyaranjan; Bhakuni, Darshan S.; Narayanan, Krishnan; Nair, Vivek; Shankar, Subramanian
Abstract Autologous hematopoietic stem cell transplant (HSCT) for rapidly progressive disease has not been reported in localized scleroderma. Our patient, a 16‐year‐old girl had an aggressive variant of localized scleroderma, mixed subtype (linear‐generalized) with Parry Romberg syndrome, with no internal organ involvement, that was unresponsive to immunosuppressive therapy and was causing rapid disfigurement. She was administered autologous HSCT in June 2011 and has maintained drug‐free remission with excellent functional status at almost 3.5 years of follow‐up.